PERUBAHAN PERILAKU SOSIAL ANAK USIA DINI SEBAGAI DAMPAK PEMBATASAN GADGET OLEH ORANGTUA DI LOMBOK TIMUR - Maulidian, Muslihatun; Filsa Era Sativa (Prodi Psikologi- Fakultas Psikologi & Humaniora - Universitas Teknologi Sumbawa, 2025)
Children's dependence on gadgets is a crucial issue that affects their social and emotional development. This study aims to examine changes in the social behavior of two children in East Lombok initials R (6 years old) and F (8 years old) following a six-month intervention involving the restriction of gadget use. This research employed a descriptive qualitative approach, using direct observation and semi-structured interviews with parents. The researcher also acted as an active observer, providing suggestions to parents regarding the regulation of their children's gadget use. The findings revealed that during the first month, the children exhibited resistance symptoms such as tantrums and social conflicts with peers. However, from the second to the sixth month, significant changes occurred: a decrease in tantrum intensity, improvement in sleep and eating patterns, increased socialization skills, and enhanced focus and academic performance. These findings affirm that consistent gadget restriction has a positive impact on children's social and emotional development, particularly in fostering self-regulation and more adaptive social interaction skills.